2014
DOI: 10.2147/jmdh.s55077
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among nurses working in the private and public sectors: a qualitative study in tertiary care hospitals in Pakistan

Abstract: BackgroundMany low and middle income countries lack the human resources needed to deliver essential health interventions. A health care system with a limited number of nurses cannot function effectively. Although the recommended nurse to doctor ratio is 4:1, the ratio in Pakistan is reversed, with 2.7 doctors to one nurse.MethodsA qualitative study using narrative analysis was undertaken in public and private tertiary care hospitals in Pakistan to examine and compare job satisfaction among nurses and understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 20 publications
6
51
0
2
Order By: Relevance
“…Besides, their knowledge about system running in clinical area would be less than others. Therefore, a study also indicated that trained healthcare working force is crucial in tertiary care hospitals of Pakistan [15].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, their knowledge about system running in clinical area would be less than others. Therefore, a study also indicated that trained healthcare working force is crucial in tertiary care hospitals of Pakistan [15].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the lack of facilities and resources of organizations in Pakistan creates a highly stressful work environment. Especially in view of the country's very high unemployment rates, employees are expected to cope with highly stressful situations in order to survive and thrive (Hamid et al, 2014). As a result of these extreme environmental work conditions, our findings may be somewhat more pronounced than if the study had been conducted in a Western context.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 72%
“…For example, all four hospitals were public sector nonprofit institutions. In comparison with public sector hospitals in more developed countries, the work context of public sector hospitals in Pakistan is highly stressful because of the scarce resources and high workload (Hamid, Malik, Kamran, & Ramzan, 2014). In addition to surveying public sector hospitals, we also targeted medium-sized companies from the manufacturing and engineering sectors because these sectors play an important role in the provision of employment in Pakistan (Ministry of Finance Pakistan, 2014).…”
Section: Methods Data Collection and Samplementioning
confidence: 99%
“…Poor salary packages with low fringe benefit also hinder the job satisfaction. As Hamid [6] study identified that the private sector attracts nurses from the public sector as they offering better pay and better working conditions. Salary should be similar for people who performing their work in similar profession and it should be determined through comparing it with the market pay rates.…”
Section: Strategies To Resolve the Organizational Problem/issuementioning
confidence: 99%
“…Strategy to deal with this problem team comprised of well balance way in term of experience and quantity as well which will help the team to work efficiently. A study done by Hamid [6] shows that "The presence of a well-trained health workforce is vital, and that certain aspects of its organization are key, including numbers (available quantity), skill mix (health team balance), and distribution (urban/rural).…”
Section: Strategies To Resolve the Organizational Problem/issuementioning
confidence: 99%